What is being conveyed to health professionals and consumers through web and print sources of nutrition information?. Issue 2 (1st October 2013) - Wills, Wendy J.; Dickinson, Angela M.; Short, Frances; Comrie, Fiona
Nutrition misinformation can be harmful. Within dietetics there is an acknowledgement that nutrition information should be consistent, science-based and made relevant to different segments of the population. This paper reports on a study, conducted in Scotland, which involved focus groups and interviews with consumers and health professionals to explore messages relating to a healthy diet and to starchy foods and foods high in fat or sugar in particular. The research also involved a discourse analysis of articles aimed at health professionals and consumers. Evidence based, clearly written web and print articles were not the norm. Many articles contained value-laden messages and inconsistent or unclear advice. Nutrition information was rarely contextualized for consumers to help them incorporate the advice into their daily lives. Consumers and health professionals reported feeling 'bombarded' by messages about diet, which was sometimes confusing. There is considerable scope for improving nutrition messaging in Scotland.